Potential utilization of renewable fuels for general internal combustion cars in the 2026 f1 engine regulations - Darmayasa, Putu Wisnu; Syah, Fiqih Firman; Hidayat, Wahyu; Fadilah, Yudan Lutfy; Supralan, Irlan; Rachman, Muchammad Irfan (Universitas Negeri Semarang, 2024)
In the automotive sector, which produces over 60-70% of global pollution emissions, the world faces difficulties in making the switch from fossil fuels to environmentally friendly renewable energy sources. Technology has advanced significantly, and companies such as Toyota and FiA are working to improve competitiveness and attract more manufacturers to produce hybrid cars. Reducing environmental impact and greenhouse gas emissions is the goal of the Formula 1 project, which partners with ARAMCO, one of the world's largest mining companies. Using the methodology of reviewing literature on energy-efficient fuels and adapting to Formula 1 vehicle regulations, with a special emphasis on hybrid strategies, to achieve net zero emissions by 2050. Research on the use of synthetic materials in fuels such as ethanol, ethanol, butanole, dimethyl methacrylate (DMM), and oxymethylethyl (OME) 3-5 has shown promising results in reducing greenhouse gas emissions. The transition to renewable energy sources is essential to reduce global pollution.